A case of hypercalcaemic crisis secondary to coexistence of primary hyperparathyroidism and Graves’ disease - Baldane S (Sciendo, 2016)
A 46 year-old female patient presented to the hospital with ongoing and progressively increasing fatigue, severe nausea and vomiting, loss of appetite, constipation, palpitations and somnolence. Laboratory evaluation revealed a severe hypercalcaemia and overt hyperthyroidism. She was diagnosed with primary hyperparathyroidism accompanied by Graves’ disease. The patient underwent total thyroidectomy and right inferior parathyroid gland adenoma excision on the 24th day of her admission to the hospital after calcium levels and free thyroid hormone levels were brought to normal ranges. We suggest that a possibility of simultaneous thyrotoxicosis and primary hyperparathyroidism in cases presenting with a hypercalcaemic crisis should be considered